SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING DI TOKO LISTRIK - Janarko, Agus Dwi; Irawati, Tri; Fitriasih, Sri Hariyati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
Madiun electricity shop is trading company which provides electricity goods. The purpose of this study is to develop a supplier selection decision support system application which is help the administrative officer to make decision based on the highest level. The simple additive weighting method applied to know each weight based on criteria and proceed with ranking which will select alternatives. The results of the research create a support system application which is select the best supplier based on the highest level. It is according to the calculations using the Simple Addtive Weighting method. The results show that the highest supplier level is on "Supplier1" with a value of "4.167". The testing method uses blackbox and validity. The result of that testing shows that there is accept on all system test scenarios. The testing validity shows that there is any comparison between old system and new system. The result of that validity testing is any comparison of the level of similarity of the selected supplier of 20% and the difference of the selected supplier of 80%, this shows significant difference between the old system and the new system. Â 